The burden of disease in early schizophrenia – a systematic literature review. (2nd January 2021) - Crespo-Facorro, Benedicto; Such, Pedro; Nylander, Anna-Greta; Madera, Jessica; Resemann, Henrike K.; Worthington, Emma; O'Connor, Molly; Drane, Emma; Steeves, Sara; Newton, Richard
Abstract: Background: Schizophrenia is a heterogeneous disorder with a burden that can vary greatly depending on the severity and the duration. Previous research has suggested that patients in the earlier stages of schizophrenia (typically first-episode schizophrenia) benefit from effective early treatment, however, a comprehensive review of the burden specifically in this population has not been undertaken. A systematic literature review was therefore conducted to characterize the clinical, economic, and humanistic burden, as reported in naturalistic studies of schizophrenia populations specifically at an early stage of disease in comparison with healthy controls, patients with chronic schizophrenia, and patients with other psychiatric disorders. Methods and materials: Searches were conducted in MEDLINE, MEDLINE In-Process, Embase, PsycINFO, and EconLit databases for records published between January 2005 and April 2019, and of relevant conference abstracts published between January 2014 and May 2019. Data were extracted from relevant publications and subjected to qualitative evaluation. Results: Fifty-two publications were identified for inclusion and revealed a considerable burden for early schizophrenia with regards to mortality, psychiatric comorbidities such as substance abuse and depression, poor social functioning, and unemployment. Comparisons with chronic schizophrenia suggested a greater burden with longer disease duration, while comparisons with other psychiatric disorders were inconclusive. This review uncovered various gaps in the available literature, including limited or no data on incarcerations, caregiver burden, and costs associated with early schizophrenia. Conclusions: Overall, the burden of schizophrenia is apparent even in the early stages of the disease, although further research is required to quantify the burden with chronic schizophrenia and other psychiatric disorders.